PENGARUH FLY ASH DAN KAPUR TOHOR TERHADAP KUALITAS AIR ASAM TAMBANG (pH dan TSS) DI PT. BARA PRIMA PRATAMA - Rahmi, Hisni; Nelvi, Afni; Situmorang, Boyman (Jurnal Teknologi Infrastruktur, 2023)
Acid mine water management can be carried out by active treatment and passive treatment. Acid mine water management in PT. Bara Prima Pratama is carried out with an active method by liming. The purpose of this study was to analyze the effect of the composition of a mixture of fly ash and quicklime as much as 0.30 grams on the pH and TSS parameters of acid mine water. The neutralization process is carried out on a laboratory scale using experimental methods with the addition of fly ash coagulant and quicklime in 9 test variations. Significant pH changes with an initial pH of 3.3 occurred at dose variations of 10:90 (1st try, pH 8.1), 20:80 (2nd try, pH 7.9) and 30:70 (3rd try, pH 7.6). This shows that to neutralize the pH requires a greater dose of quicklime in the composition of the mixture (quicklime can increase the pH value quickly). Furthermore, TSS testing was also carried out 9 times with an initial TSS value of 123 mg/L. After neutralization was obtained, the TSS value continued to increase in proportion to the composition carried out (test 9, TSS value 219 mg/L) but still met environmental quality standards with a threshold value of 400 mg/L. This shows that the use of fly ash and quicklime does not have a major effect on TSS changes.